FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEGAGALAN PEMBERIAN ASI EKSKLUSIF PADA BAYI DI WILAYAH KERJA PUSKESMAS DARUL IMARAH KABUPATEN ACEH BESAR TAHUN 2023 - Agusti, Nurfillah; Susanti, Dewina; Mauliati, Desria; Dewi, Rika; Fachriani, Faulina; Herlina, Sri; Ariska, Nova (JURNAL ILMIAH DHDT - KEBIDANAN, 2023)
The low coverage of exclusive breastfeeding success in infants of 61.1% is caused by various factors such as factors of public knowledge and attitudes towards health, culture and community beliefs such as peucicap, breast milk, education, family support and maternal employment. The purpose of the study was to determine the factors associated with the failure of exclusive breastfeeding in infants aged 0-6 months in the Working Area of the Darul Imarah Health Center, Aceh Besar Regency in 2023. This research method is analytic with a Cross Sectional approach with a Random Sampling technique with a sample size of 83 people. This research was conducted on June 8 to 15, 2023 with univariate and bivariate analysis with the Chi square test. The results showed that of the 83 respondents most did not provide exclusive breastfeeding as many as 48 respondents (57.8%), had poor knowledge as many as 33 respondents (39.8%) with a p value of 0.001, there were no breast milk expressing as many as 48 respondents (57.8%) with a p value of 0.002, there were peucicap as many as 48 respondents (57.8%) with a p value of 0.001, did not support as many as 44 respondents (53%) with a p value of 0.007. Conclusions and suggestions there is a relationship between knowledge, breast milk expressing, peucicap and family support with the failure of exclusive breastfeeding. It is hoped that respondents will increase their knowledge and motivation by exploring information about exclusive breastfeeding from various sources such as health workers and books, so that mothers can provide exclusive breastfeeding.